Analisis Hubungan Perilaku Konsumen Terhadap Keputusan Pembelian Produk Hampers (Studi Kasus Toko Le Chic Parfait dan Bakehouse) - Hidayah Yoanna Putri (Cattleya Darmaya Fortuna, 2024)
PT Boga Abadi Prima is a company engaged in the culinary industry which was established specifically to manage Le Chic Parfait and Bakehouse restaurants which are currently one of the culinary creative industry sectors that not only provide cakes and drinks but also open Hampers business opportunities that aim to meet consumer needs at certain moments, such as holidays and birthday celebrations of coworkers or offices. As the hampers business develops, competition is getting tougher, so companies need to understand consumer behavior. Consumer behavior is very diverse and can change at any time. Therefore, it is important for companies to pay attention, understand, and establish an approach to these various consumer behaviors, so as to identify factors that influence purchasing decisions. Consumer behavior includes the reasons and motivations of consumers in buying, using, and consuming products, as well as the factors that influence purchasing decisions and product use. Factors that influence consumer behavior include cultural, social, personal, and psychological factors. This research uses quantitative methods, with validity, reliability, product moment correlation, and T test as a measure of success. The results showed that consumer behavior has a strong relationship to purchasing decisions with a Pearson Correlation value for Consumer Behavior of 0.634 and a Pearson Correlation of Purchasing Decisions of 0.634. Cultural factors recorded the highest value in a strongly agree response to product purchasing decisions at Le Chic Parfait and Bakehouse Stores, with an average value of 4.26 and a percentage of 26%. It is hoped that Le Chic Parfait and Bakehouse Stores can maintain cultural factors and improve social factors by increasing Brand Awareness so that buyers more easily recognize and promote Le Chic Bakehouse products.